Application des pesticides en agriculture maraichère au Togo - Madjouma Kanda; Gbandi Djaneye-Boundjou; Kpérkouma Wala; Kissao Gnandi; Komlan Batawila; Ambaliou Sanni; Koffi Akpagana (VertigO)
The study focuses on the analysis of practices, attitudes and knowledge of gardening in relation to of pesticides use in Togo. It covered the five (5) administrative regions of the country by a structured survey of 297 gardeners. 98 % of them agree that the use of pesticides reduces losses due to pests and ensure good performance. However, the decision to perform pesticide treatments and the times of treatment differs from one gardener to another and from one region to another. Use patterns and deficiency periods are not under control. Gardeners mostly poorly trained (14 %) do not have a good knowledge of application rates and frequencies of treatment. They are less convinced by direct risks they face and thereby rarely protect themselves.